Russia’s Strategy on Strengthening Its Cooperations with the Middle East Countries after Russia-Ukraine War in 2022 - Gihoni, Okvivio Vergina; Nugrahani, Henny Saptatia Drajati (UI Scholars Hub, 2024)
ABSTRACT. This research discusses the extension of the conflict between two nations, namely Russia and Ukraine, in 2022. The ongoing tensions between these countries, dating back to 2014 and escalating into a designated military operation declared by Russia in 2022, have precipitated a global crisis. With other nations becoming affected actors, leading to fluctuations in energy prices and a surge in refugee numbers, numerous efforts have been made by many countries, including major global players. Western nations have imposed a series of sanctions on Russia, and Russia has reciprocated in response to these sanctions. Russia has adopted several strategies to endure, with one notable effort being the strengthening of partnerships with various countries in the Middle East. Utilizing qualitative research methods, this study explores Russia's collaboration with Middle Eastern nations as a response to the sanctions imposed by what Russia terms as unfriendly countries. This encompasses changes in Russia's geopolitical and geostrategic landscape, as well as the motivations behind Russia's pursuit of alternative collaborations with non-Western countries across various sectors, from critical to less politically sensitive domains.